Simulasi Pencitraan Logam dengan Antena Bowtie Terkopel Bolometer pada Radiasi Gelombang THz - Catur Apriono; Hendry Steven Marbun (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Air transportation is one of transportation modes with a significant increase in the number of passengers. However, air transportation sometimes is threatened by terrorism act and sabotages, mostly caused by negligence in detecting dangerous metal items. THz wave can be used as imaging because it is safe and has a high spatial resolution. However, THz waves are vulnerable to diffraction. In this paper, diffraction studies and metal imaging simulations of THz waves were carried out using CST Microwave Studio software. The simulation used a bowtie antenna-coupled bolometer as a sensor, due to its simple design and wide bandwidth. Simulations were carried out with various types of antennas with working frequencies of 1 THz, 3 THz, and 5 THz. Variations of plane wave polarization (Ex and Ey polarization) were also performed for each type of antennas. Simulations with increased frequency produce more accurate images because they have smaller diffraction effect and greater spatial resolution. Simulations with Ex polarization produces a better image in contrast because it has a parallel movement of the electric field with the sensor.